Analysis of the Effects of Financial Performance on Dividend Policy (A Case Study of Material Companies Listed on the Indonesia Stock Exchange in the 2019-2023 Period) - Ningtiyas, Tiara Zumarroh; Galuh, Ajeng Kartika (Contemporary Studies in Economic, Finance and Banking, 2025)
The optimal dividend policy is one that maximizes the balance between dividend distribution and investment allocation to foster sustainable development. In a formulating this policy, management must take into consideration the interests of shareholders and the company’s long-term viability, while also accounting for various factors that influence dividend decisions, particularly financial performance. Accordingly, this research aims to examine the impact of financial performance on dividend policy. The sample was selected through purposive sampling, targeting companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The data were analyzed using panel data regression. The outcome of this research revealed that CR positively affects dividend policy, whereas ROA and TATO exert a negative effect. Meanwhile, DER and firm size show no a significant effect on dividend policy.